2015
DOI: 10.1590/0034-7167.2015680104p
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e atividade física em profi ssionais de terapia intensiva do sub médio São Francisco

Abstract: Objective: the objective was to assess the level of physical activity (LPA) and the quality of life QL of the professionals who work in ICU. Method: this was a cross-sectional study carried out in Adult ICUs. LPA was assessed by the International Questionnarie of Physical Activity -short form (IQPA-SF) and the QL by the Medical Outcomes Study 36 (SF-36) questionnaire. Results: it was classifi ed active 50.89% out of a total of 59 professionals. Nursing technicians were considered the most active with 60.6%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
6
0
14
Order By: Relevance
“…In a close reality, the Freire et al (2015) research with 59 professionals of Pernambuco and Bahia showed similar results in the areas of functional functionality(PF), pain(BP), Emotional aspects(RE) and superiority of the health related quality of life measure. In the areas of Physical aspects(RP), Vitality(VT), Social Function(SF) and general health state(GH), area with the most discrepant scores, because while the Freire et al (2015) research was 83,20 score, the Salvador one had a 55,67 score, signaling a bad health related quality of life.…”
Section: Discussionmentioning
confidence: 73%
“…In a close reality, the Freire et al (2015) research with 59 professionals of Pernambuco and Bahia showed similar results in the areas of functional functionality(PF), pain(BP), Emotional aspects(RE) and superiority of the health related quality of life measure. In the areas of Physical aspects(RP), Vitality(VT), Social Function(SF) and general health state(GH), area with the most discrepant scores, because while the Freire et al (2015) research was 83,20 score, the Salvador one had a 55,67 score, signaling a bad health related quality of life.…”
Section: Discussionmentioning
confidence: 73%
“…Silva; Queiroz (2011) abrandam que a maior parte das pesquisas enfatizam o estresse no trabalho nos profissionais da saúde, entretanto com os duplos cargos pela modalidade de trabalho por divisão de plantões, as pessoas tendem a diminuir o tempo das atividades física e de lazer (FREIRE et al, 2015). Podemos supor que, esse elevado número de sujeitos do estudo que não praticam atividade física classificados pelo instrumento IPAQ possuam o motivo descrito por Faria Júnior (1990) e Silva; Queiroz (2011) ou devido a atividades domésticas.…”
Section: Discussionunclassified
“…A carga horária de serviço também pode interferir negativamente na vida do trabalhador, fazendo com que os trabalhadores diminuam seu tempo de sono, desenvolvimento de doenças, como estresse e obesidade, além de não encontrarem tempo para o lazer ou atividade física (PAFARO; MARTINO, 2004;MORENO;ROTENBERG, 2003;SILVA et al, 2010;FREIRE et al, 2015). É importante ressaltar que a ausência de atividade fí-sica, a prevalência de doenças crônicas, aumento do quadro de morbimortalidade estão relacionados às modificações e organizações do mercado trabalho (CAVALCANTE et al, 2006;FREIRE et al, 2015), que interferem negativamente na qualidade de vida do trabalhador.…”
Section: Introductionunclassified
“…Foi encontrada diferença estatisticamente significativa entre as instituições apenas no item Recursos Mentais, no qual o grupo do H1 denotou apreciar menos as atividades diárias que realiza e no H2 foi evidenciada menor esperança no futuro. Nas comparações entre categorias funcionais inter e entre hospitais quanto à QV e CT foram encontradas diferenças estatisticamente significativas particularmente entre técnicos de enfermagem e médicos A relação entre QV e CT da população pesquisada, como um todo, foi positiva e significativa, sendo que a correlação mais forte encontrada foi entre o ICT e o maiores índices de absenteísmo e presenteísmo, além de problemas de recrutamento, retenção ou rotatividade do pessoalo que encarece e dificulta a gestão das instituições de saúde públicas e privadas (FERREIRA et al 2015;ROSA, 2015).…”
unclassified